The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/life12081259
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Nanosecond Dynamics of Pathologically Relevant Bio-Macromolecules Observed by Incoherent Neutron Scattering

Abstract: Incoherent neutron scattering (iNS) is one of the most powerful techniques to study the dynamical behavior of bio-macromolecules such as proteins and lipid molecules or whole cells. This technique has widely been used to elucidate the fundamental aspects of molecular motions that manifest in the bio-macromolecules in relation to their intrinsic molecular properties and biological functions. Furthermore, in the last decade, iNS studies focusing on a possible relationship between molecular dynamics and biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 81 publications
0
4
0
Order By: Relevance
“…Unlike the above models, the dynamical behaviors of these atoms were defined in advance using the diffusion-inside-asphere model and the jump-diffusion model, which are normally employed in QENS studies of proteins. 4,42 Since these two models have an intrinsic Q-dependence, global fitting, where all the spectra at all the Q values are fitted simultaneously, was employed against the simulated QENS data in this study. Moreover, a few prior considerations were necessary for successful fitting: from several trials of the global fitting, it was found that it is necessary to fix the a HM value in advance due to a large number of fitting parameters, and that a HM needs to be smaller than a LM because as a HM increases, i.e., the a HM value becomes closer to the a LM value, the fitting fails with some dynamical parameters taking negative values.…”
Section: Application Of the CDL Modelmentioning
confidence: 99%
“…Unlike the above models, the dynamical behaviors of these atoms were defined in advance using the diffusion-inside-asphere model and the jump-diffusion model, which are normally employed in QENS studies of proteins. 4,42 Since these two models have an intrinsic Q-dependence, global fitting, where all the spectra at all the Q values are fitted simultaneously, was employed against the simulated QENS data in this study. Moreover, a few prior considerations were necessary for successful fitting: from several trials of the global fitting, it was found that it is necessary to fix the a HM value in advance due to a large number of fitting parameters, and that a HM needs to be smaller than a LM because as a HM increases, i.e., the a HM value becomes closer to the a LM value, the fitting fails with some dynamical parameters taking negative values.…”
Section: Application Of the CDL Modelmentioning
confidence: 99%
“…For more complicated models, functions returning the Q-dependence of the half-width at half maximum (HWHM), the elastic incoherent structure factor (EISF) and the quasi-elastic incoherent structure factors (QISF) for the 1D peak are also provided. We refer to [8,18] for definitions of these terms.…”
Section: Software Architecturementioning
confidence: 99%
“…CC-BY 4.0 International license perpetuity. It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted September 12, 2022. ; https://doi.org/10.1101/2022.09.08.507213 doi: bioRxiv preprint in light of functional aberration of proteins, i.e., human diseases and disorders, has emerged during the last decade ( [13] and references therein). This trend, which is associated with molecular physiology and pathology, emphasizes more than ever the importance to interpret QENS data in association with protein functions, which are determined in light water environments.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have focused on the dynamicsfunction relationship of proteins such as bacteriorhodopsin [7][8][9][10] and those in photosystem II membrane fragments [11,12]. In addition to this, a new research trend focusing on protein dynamics in light of functional aberration of proteins, i.e., human diseases and disorders, has emerged during the last decade ( [13] and references therein). This trend, which is associated with molecular physiology and pathology, emphasizes more than ever the importance to interpret QENS data in association with protein functions, which are determined in light water environments.…”
Section: Introductionmentioning
confidence: 99%